Usefulness of vitamin C in critically ill patients: a systematic review - Sousa do Nascimento, Karoline; Lipoyestky, Fernando (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Introduction: Vitamin C, also known as ascorbic acid, is an essential micronutrient that plays a key role in fighting systemic inflammation in critically ill patients. Low levels of this vitamin are common in critically ill individuals due to increased oxidative stress. The objective of this study is to investigate and evaluate the use of vitamin C in critically ill patients admitted to intensive care units, with the purpose of identifying its advantages and limitations, and determining its effectiveness in reducing mortality in this group of patients. Methods: the present study is a systematic review; previously published articles were searched in the PubMed database. The research was carried out at the university level. 14 results were obtained. Results: results from clinical and observational studies have been controversial, but some reports suggest improvements in organ function, shorter ICU stays, and reduced mortality in certain patient groups. Other studies did not show a significant change in mortality to justify the use of vitamin C therapy. Conclusion: controversy regarding clinical results persists; monotherapy with high doses of vitamin C presents a biologically acceptable justification. While we wait for more results, it is important to ensure that critically ill patients receive the recommended dose of vitamin C to keep their immune and metabolic function optimized and ensure daily intake for healthy people